Clinical Features and Outcomes of 124 Italian Patients With Treatment Resistant Depression: A Real-World, Prospective Study - Perugi, Giulio; Calò, Paola; De Filippis, Sergio; Rosso, Gianluca; Vita, Antonio; Adami, Marina; Ascione, Giuseppe; Morrens, Joachim; Delmonte, Dario (Frontiers in Psychiatry, 2021)
Introduction: Treatment-resistant depression (TRD) is a debilitating condition affecting 20-30% of patients with major depressive disorders (MDD). Currently, there is no established standard of care for TRD, and wide variation in the clinical approach for disease management has been documented. Real-world data could help describe TRD clinical features, disease burden, and treatment outcome and identify a potential unmet medical need. Methods: We analyzed the Italian data from a European, prospective, multicentric, observational cohort study of patients fulfilling TRD criteria by the European Medicine Agency, with moderate to severe major depressive episode, and starting a new antidepressant treatment according to routinary clinical practice. They were followed up for minimum 6 months. Treatments received throughout the study period, disease severity, health-related quality of life and functioning were prospectively recorded and analyzed. Results: The Italian subcohort included 124 TRD patients (30.2% of patients of the European cohort; mean age 53.2 [sd=9.8], women: 82, 66.1%). At enrollement, the mean (SD) duration of MDD was 16 years (sd=11.1) and the mean duration of the ongoing major depressive episode (MDE) was 97.5 weeks (sd=143.5); low scores of quality of life and functioning were reported. The most frequently antidepressant classes started at baseline (data available for 98 subjects) were selective serotonin reuptake inhibitors (SSRI, 42 patients [42.9%]) and serotonin-norepinephrine reuptake inhibitors (SNRI, 32 patients [32.7%]). In terms of treatment strategies, 50 patients (51%) started augmentation therapies, 18 (18.4%) combination therapies and 24 (24.5%) monoterapies (6 patients [6%] started a non-antidepressant drug only). Fourteen patients (11.3%) were treated with a psychosocial approach, including psychotherapy. After 6 months of treatment, clinical assessments were collected for 89 patients: 64 (71.9%) showed no response, 9 (10.1%) response without remission and 16 (18.0%) were in remission; accordingly, non-responder patients showed lower quality of life and higher disability scores than responder patients. Conclusions: In our sample of TRD patients, we documented a substantial illness burden, low perceived quality of life and poor outcome, suggesting an unmet treatment need in TRD care in Italy.